Aryne Reaction with γ‐Arylallenylcarboxyamides: Unexpected Diels–Alder Cycloaddition. Issue 7 (27th April 2015) - Fu, Haixing; Yang, Yupo; Wei, Zhibin; Zhang, Zhengjuan; Wu, Chunrui; Shi, Feng
Abstract When γ‐arylallenylcarboxyamides react with arynes, their arylallene moiety reacts in a Diels–Alder fashion, leaving the amide functionality intact.